2002
DOI: 10.1146/annurev.immunol.20.100301.064828
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Presentation and T Cell Stimulation by Dendritic Cells

Abstract: Dendritic cells take up antigens in peripheral tissues, process them into proteolytic peptides, and load these peptides onto major histocompatibility complex (MHC) class I and II molecules. Dendritic cells then migrate to secondary lymphoid organs and become competent to present antigens to T lymphocytes, thus initiating antigen-specific immune responses, or immunological tolerance. Antigen presentation in dendritic cells is finely regulated: antigen uptake, intracellular transport and degradation, and the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
1,272
0
55

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,627 publications
(1,342 citation statements)
references
References 317 publications
15
1,272
0
55
Order By: Relevance
“…Studies have shown that APC residing both in the intestinal lamina propria and in the MLN have distinct tolerogenic properties and that their antigen presenting ability favours development of Treg [44]. A tolerogenic APC lacks the complete range of co-stimulatory molecules necessary for full T-cell activation and APC with a tolerogenic potential has the capacity to present an antigen to a naïve T cell in such a manner that it is converted to a Treg [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that APC residing both in the intestinal lamina propria and in the MLN have distinct tolerogenic properties and that their antigen presenting ability favours development of Treg [44]. A tolerogenic APC lacks the complete range of co-stimulatory molecules necessary for full T-cell activation and APC with a tolerogenic potential has the capacity to present an antigen to a naïve T cell in such a manner that it is converted to a Treg [45].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that APC residing both in the intestinal lamina propria and in the MLN have distinct tolerogenic properties and that their antigen presenting ability favours development of Treg [44]. A tolerogenic APC lacks the complete range of co-stimulatory molecules necessary for full T-cell activation and APC with a tolerogenic potential has the capacity to present an antigen to a naïve T cell in such a manner that it is converted to a Treg [45].In conclusion, we show here that mice neonatally pretreated with S. aureus superantigen (SEA) improve their oral tolerance mechanism. Further studies are needed to dissect the involved mechanisms behind the remarkably longlasting effect of neonatal SEA administration, which act in favour of oral tolerance.…”
mentioning
confidence: 99%
“…There is substantial evidence that the professional APC, that are crucial in T cell activation, are dysfunctional early in life [47]. Naive T cells require prolonged signaling through the TCR and increased costimulation, and are thus mainly stimulated by dendritic cells (DC) of the myeloid lineage [48,49]. Several groups have demonstrated that DC from both human cord-blood [50], and neonatal mice [51] show decreased capacity of antigen presentation and stimulation of CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction DC, one of the earliest cell types exposed to pathogens, are the most potent APC with a unique ability to induce primary immune responses against microbial infection [1][2][3]. First, immature DC capture the pathogen via high endocytic and phagocytic activities, and then they migrate to regional LN where they develop into mature DC through interaction of TLR and the microbial products, and become APC able to activate Ag-specific naive lymphocytes [4].…”
mentioning
confidence: 99%